2014
DOI: 10.1615/intjmedmushr.v16.i2.60
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Expression Plasmid and its Use in Genetic Manipulation of Lingzhi or Reishi Medicinal Mushroom, Ganoderma lucidum (Higher Basidiomycetes)

Abstract: We report the construction of a plasmid, pJW-EXP, designed for the expression of homologous and heterologous genes in Ganoderma lucidum. pJW-EXP was generated from the plasmid pMD19-T by inserting the G. lucidum glyceraldehyde-3-phosphate dehydrogenase gene promoter, the G. lucidum iron-sulfur protein subunit of succinate dehydrogenase gene terminator and the homologous carboxin-resistance gene as selection marker. This expression plasmid can be efficiently transformed into Ganoderma through polyethylene glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 11 publications
1
38
0
Order By: Relevance
“…The preparation of G. lucidum protoplasts and PEG‐mediated genetic transformation were conducted as previously described (Xu et al , , ; Yu et al , ). Transformants were screened using carboxin (2 mg l −1 ) or phosphinothricin (150 mg l −1 ) on a CYM regeneration plate.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of G. lucidum protoplasts and PEG‐mediated genetic transformation were conducted as previously described (Xu et al , , ; Yu et al , ). Transformants were screened using carboxin (2 mg l −1 ) or phosphinothricin (150 mg l −1 ) on a CYM regeneration plate.…”
Section: Methodsmentioning
confidence: 99%
“…Mitotic stability analysis revealed that the introduced DNA is stably integrated in the genome of transformants obtained through ATMT and PMT methods. 6,8,9 The reproducibility of the ATMT and PMT methods have also been confirmed through the overexpression of different G. lucidum homologous genes. [8][9][10][11][12] PMT, REMI and electroporation methods usually result in the ectopic integration of DNA into the genome of G. lucidum with one or more copy numbers.…”
mentioning
confidence: 83%
“…We previously developed a selection marker gene cbx R on the basis of a host-derived gene rather than heterologous genes; we then used cbx R to establish a stable genetic transformation system for G. lucidum. [8][9] Molecular hybridization analysis revealed that cbx R is stably integrated in the genome of the transformants. Moreover, the established homologous transformation system has been successfully used to overexpress 3-hydroxy-3-methyL-glutaryl coenzyme A reductase gene, 9 squalene synthase gene, 10 a-phosphoglucomutase gene, 11 and UDP glucose pyrophosphorylase gene 12 in G. lucidum.…”
mentioning
confidence: 99%
See 2 more Smart Citations